Penyelesaian Sengketa Hak Ulayat pada Kawasan Hutan - Adonia Ivonne Laturette (Faculty of Law, Universitas Pattimura, 2021)
Customary law communities are one of the legal subjects of the state that are recognized in statutory regulations. Customary law communities have a multidimensional relationship with customary rights, not just an economic resource, but an integral part of the overall life of the customary law community. This research aims to study and analyze the settlement of disputes by indigenous peoples over land exploitation which is customary rights in the Forest Zone. The research method used in this research is normative juridical research, namely the method of doctrinal law research by examining and examining the provisions of the applicable laws and regulations as a basis for later analyzing the problems being studied. Based on the results of the research that the importance of the role of land in human life, land becomes an object that is prone to disputes or disputes between humans, this happens because human needs for land are increasing, land can cause disturbances and involve the community at large, so it is demanded to handle it appropriately. The parties involved and authorized to deal with the issue of customary rights in the forest area of indigenous peoples, resolve it in various ways. The method of dispute resolution that has been taken so far is through court (litigation). Over time, dispute resolution through deliberation is increasingly being carried out. Land disputes, which are more related to issues of interest or interest of the parties, are relatively easier to resolve through deliberation as long as both parties are open to each other and want the best solution for all parties.